Workshop and Training on Bouquet Crafts to Build Entrepreneurs of PKK Mothers in Srondol Kulon Village - Moehammad Istbat Robbaney (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The bouquet making training for the Srondol Kulon village community aims to improve and hone the skills of the Srondol Kulon Village residents, especially PKK mothers. With this bouquet training, it is hoped that it can foster an entrepreneurial spirit and improve MSMEs which can boost the economy of the residents of Srondol Kulon Village. The implementation of training in making bouquet crafts among the residents of Srondol Kulon Village, the community had high enthusiasm and had a positive impact on the community's ability to make crafts from feather wire bouquets. By providing training on making feather wire bouquet crafts to PKK mothers, it is hoped that new entrepreneurs will be born who are able to innovate and be competitive in marketing feather wire bouquet craft products.